2014
DOI: 10.1017/s1047951114000304
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in adolescents with congenital heart disease

Abstract: Type of congenital heart disease and initial diagnosis did not seem to affect the perception of health-related quality of life, corroborating findings of several studies. Surgical interventions and the use of medication can improve previous clinical status, and therefore it seems to be beneficial in terms of Psychological Well-Being. The presence of clinical symptoms was the variable that caused the largest impact on the perception of health-related quality of life, possibly because of the impairment they brin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 29 publications
2
33
1
2
Order By: Relevance
“…Similarly, our results also showed that disparities in being able to do things other children do may increase with age. As children with CHD age, cognitive deficits and functional limitations may become more apparent and lead to lower physical and psychosocial quality of life . However, interventions shown effective among other CSHCN, such as structured computerized training programs, mindfulness training, occupational therapy, aerobic exercise, and special education services may prevent or mitigate functional limitations in children with heart disease and improve educational and social outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, our results also showed that disparities in being able to do things other children do may increase with age. As children with CHD age, cognitive deficits and functional limitations may become more apparent and lead to lower physical and psychosocial quality of life . However, interventions shown effective among other CSHCN, such as structured computerized training programs, mindfulness training, occupational therapy, aerobic exercise, and special education services may prevent or mitigate functional limitations in children with heart disease and improve educational and social outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…1 In the literature, there are an increasing number of studies elaborating even further the notions of mortality and morbidity by considering real-time data for reported long-term physical functioning, quality of life, health perceptions, and psycho-social well-being. [2][3][4][5][6][7][8] In addition, there is evidence that the presence of CHD can have a direct impact on the child's physical, motor, cognitive, and neurological development; 1 however, the conflicting results from current research, concerning quality-of-life issues in children with CHD, reveal a lack of methodological and conceptual rigour. 1 Nevertheless, despite any limitations, a number of studies try to identify determinants of quality of life in this heterogeneous group of patients with cardiac malformations including acyanotic, cyanotic, and obstructive heart defects.…”
Section: O Ver the Last Few Decades Due To The Improvedmentioning
confidence: 99%
“…[2][3][4][5][6][7][8] In addition, there is evidence that the presence of CHD can have a direct impact on the child's physical, motor, cognitive, and neurological development; 1 however, the conflicting results from current research, concerning quality-of-life issues in children with CHD, reveal a lack of methodological and conceptual rigour. 1 Nevertheless, despite any limitations, a number of studies try to identify determinants of quality of life in this heterogeneous group of patients with cardiac malformations including acyanotic, cyanotic, and obstructive heart defects. [9][10] Congenital heart defect refers to a wide spectrum of simple, moderate, and complex lesions, caused by abnormal heart development during endometrial life.…”
Section: O Ver the Last Few Decades Due To The Improvedmentioning
confidence: 99%
“…Although the presence of cyanotic heart disease was associated with poorer psychosocial health in this study, data from other studies are conflicting. 21,28 These mixed findings may be due to the lack of uniformity in reporting severity of disease and the heterogeneous complexity of surgery. Unlike others, we did not find an association with socio-economic status 3,17,2,24 or need for medications.…”
Section: Discussionmentioning
confidence: 99%